PENYUTRADARAAN DENGAN PENDEKATAN DIRECTOR AS ACTOR UNTUK MENDUKUNG AKTING PRESENTASI DALAM FILM RUMONDANG - afridah hayati (Institut Seni Indonesia Padang Panjang, 2025)
Film is the right medium to convey a messages to the wider community. Rumondang is afictional social drama genre film with 16 scenes and 17 minute film. The film Rumondang tells the story of a woman named Rumondang who has hullucinations of her husband died. The author realizes the Rumondang character.To realize the concept of presentation acting, the author uses the theory of supporting directer as actor where the director as an actor with the aim that the actor will better understand what the director wants, but the actor does not have to imitate the whole actor as well as the opportunity to participate in thinking and developing what the director demonstrates. The concept of presentation acting is applied by the author in several scenes in the film. Actors must also be able to present natural acting which means reasonable acting and can convience the audiece.